Thoracolumbar fascia deformation during deadlifting and trunk extension in individuals with and without back pain - Brandl, Andreas; Wilke, Jan; Egner, Christoph; Reer, Rüdiger; Schmidt, Tobias; Schleip, Robert (Frontiers in Medicine, 2023)
Background: Alterations in posture, lumbopelvic kinematics, and movement patterns are commonly seen in patients with low back pain. Therefore, strengthening the posterior muscle chain has been shown to result in significant improvement in pain and disability status. Recent studies suggest that thoracolumbar fascia (TLF) has a major impact on the maintenance of spinal stability and paraspinal muscle activity, and thus is likely to have an equal impact on deadlift performance. Objective: Aim of the study was to evaluate the role of thoracolumbar fascia deformation (TFLD) during spinal movement in track and field athletes (TF) as well as individuals with and without acute low back pain (aLBP). Methods: A case-control study was performed with n=16 aLBP patients (cases) and two control groups: untrained healthy individuals (UH, n=16) and TF (n=16). Participants performed a trunk extension task (TET) and a deadlift, being assessed for erector spinae muscle thickness (EST) and TLFD using high-resolution ultrasound imaging. Mean deadlift velocity (VEL) and deviation of barbell path (DEV) were measured by means of a three-axis gyroscope. Group differences for TLFD during the TET were examined using ANOVA. Partial Spearman rank correlations were calculated between TLFD and VEL adjusting for baseline covariates, EST, and DEV. TLFD during deadlifting was compared between groups using ANCOVA adjusting for EST, DEV, and VEL. Results: TLFD during the TET differed significantly between groups. TF had the largest TLFD (–37.6%), followed by UH (–26.4%), while aLBP patients had almost no TLFD (–2.7%). There was a strong negative correlation between TLFD and deadlift VEL in all groups (r=–0.65 to –0.89) which was highest for TF (r=–0.89). TLFD during deadlift, corrected for VEL, also differed significantly between groups. TF exhibited the smallest TLFD (–11.9%), followed by aLBP patients (–21.4%), and UH (–31.9%). Conclusion: TFLD maybe a suitable parameter to distinguish LBP patients and healthy individuals during lifting tasks. The cause-effect triangle between spinal movement, TFLD and movement velocity needs to be further clarified.